The interaction effect of earnings and dividend / Nurulashikin Lokman - Lokman, Nurulashikin (2007)
This study is to examine the interaction effect of earnings and dividends whether both earnings and dividends provide information to each other. Dividend is a signal to investors where increases in dividend is associated with positive abnormal returns and decreases in dividend is associated with negative abnormal returns around the time of the dividend announcements. A lower or negative in earnings does not necessary indicate a bad news to investors. A sample of 251 Syariah Compliance firms listed on main boards in Bursa Malaysia was chosen for this study over the year 2001 to 2005. Regression model has been employed to test whether an interaction effect exist between earnings and dividends. The expected result of the interaction test is significant, indicating that both signals jointly influenced the level of abnormal returns earned by the companies. It shows that there are an interaction effect exists between earnings and dividends.